Appropriateness of devices in the surgical treatment of femoral shaft fractures - Biserni, Michele; Talesa, Giuseppe Rocco (Lo Scalpello - Journal, 2020)
Femoral shaft fractures occur mainly due to high-energy traumas. To date, osteosynthesis represents the gold standard for the treatment of such fractures, and may be undertaken with a variety of stabilization methods: endomedullary nailing, plating, external fixation. However, there is no EBM literature unequivocally addressing a treatment for this topic. In order to appropriately treat femoral shaft fractures the authors believe it is essential to consider the pattern of lesion from an anatomo-pathological viewpoint, to evaluate the fracture pattern and put in relation to the patient’s conditions, pointing out that surgical versatility, trauma experience and skills and the appropriateness in choosing the devices of synthesis is essential to approach such lesions.